2006
DOI: 10.1037/0278-7393.32.3.609
|View full text |Cite
|
Sign up to set email alerts
|

Study efficacy and the region of proximal learning framework.

Abstract: One of the most important reasons to investigate human metacognition is its role in directing how people study. However, limited evidence exists that metacognitively guided study benefits learning. Three experiments are presented that provide evidence for this link. In Experiment 1, participants' learning was enhanced when they were allowed to control what they studied. Experiments 2a-d replicated this finding and showed contributions of self-regulated study to learning. Experiments 3a and 3b showed that, when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
218
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 198 publications
(232 citation statements)
references
References 54 publications
8
218
3
3
Order By: Relevance
“…For instance, Kornell and Metcalfe (2006) asked participants to choose which half Forward testing effect 7 of a set of word pairs they preferred to restudy later. In the honouring condition, participants reviewed the pairs which were selected to be restudied.…”
Section: Self-regulated Learningmentioning
confidence: 99%
“…For instance, Kornell and Metcalfe (2006) asked participants to choose which half Forward testing effect 7 of a set of word pairs they preferred to restudy later. In the honouring condition, participants reviewed the pairs which were selected to be restudied.…”
Section: Self-regulated Learningmentioning
confidence: 99%
“…To be considered temporarily learned a word had to be answered correctly, on the first try, on two separate occasions. In this way, the focus was put on the words that the participant had not learned, and time and effort were not wasted on words they already knew (see Kornell & Metcalfe, 2006;Metcalfe & Kornell, 2005, for more details concerning the efficacy of this strategy).…”
Section: Training (Sessions 2-5)mentioning
confidence: 99%
“…According to the agenda-based regulation framework (Ariel, Dunlosky, & Bailey, 2009), students are developing an agenda-or simple plan-to help them maximize performance. This particular agenda has been called using a region of proximal learning (RPL; Metcalfe, 2002), and using it can improve learning (Kornell & Metcalfe, 2006). Recently, however, Dunlosky and Ariel (in press) reported that how materials were presented influenced students' item selections and undermined their use of an RPL agenda.…”
mentioning
confidence: 99%